Sosialisasi Persiapan Program Beasiswa Pendidikan Ke Luar Negeri bagi Anggota Karang Taruna Youngunter - Desy Awal Mar'an; Anwar Fadila; Nita Sitta Rachma; Muhammad Ubaidillah; Nabila Hasri Ainun (Ruang Pengabdian: Jurnal Pengabdian kepada Masyarakat, 2025)
Education is one of the strategic efforts to improve the quality of human resources, particularly through the equitable distribution of access to educational scholarships. However, in practice, many young people still lack adequate information regarding overseas educational scholarships. Therefore, efforts are needed to disseminate information about international scholarships through socialization activities. This community service program aims to enhance youths’ understanding of various overseas scholarship opportunities and the requirements that need to be prepared from an early stage. This activity employed a descriptive qualitative approach, focusing on youths’ perceptions of the implementation of an overseas scholarship socialization program. The activity was conducted at the Community Hall of Gunung Terang Sub-district, Bandar Lampung, involving 13 youth members of Karang Taruna Youngunter. Data were collected through open-ended questionnaires and post-activity interviews with the participants. The data were analyzed using thematic analysis to identify changes in perceptions, levels of understanding, and participants’ motivation. The outcomes of the program were assessed based on indicators including increased knowledge of scholarship types and requirements, enhanced motivation to prepare for scholarship applications, and heightened awareness of the importance of early preparation. The findings indicate improvements in participants’ understanding and motivation, as well as the emergence of an action-oriented mindset in planning initial steps for overseas educational scholarship preparation, suggesting that this activity has the potential to serve as an initial model of youth empowerment at the community level.